172. Predictors of cardiac dose reduction achieved with deep inspiration breath hold technique over free breathing technique in left breast radiotherapy. (December 2018) - Maddalo, M.; Benecchi, G.; Grondelli, C.; Calabri, E.; Rossi, R.; Losardo, P.; Bergamini, M.L.; Dell'Anna, C.; Ceccon, G.; Nurmahomed, S.; Gianni, S.; Rossi, R.; et al.
Abstract: Purpose: Deep inspiration breath-hold (DIBH) has been routinely applied in left breast radiotherapy to reduce cardiac exposure. The purpose of this study was to compare deep inspiration breath hold and free breathing techniques (FB) in terms of heart and left-lung doses and to determine possible predictors of the dose reduction achieved with DIBH ( Δ DBH-FB). Methods: Ten patients with left breast cancer have been treated with postoperative radiotherapy in Parma Hospital. For each patient both the FB and the DIBH planning CT were acquired. 3DCRT treatment plans using tangential field-in-field beams were developed for both FB and DIBH. FB and DIBH dose distributions were compared in terms of Dmean, V5Gy, V20Gy, V30Gy of the heart and V5Gy, V20Gy of the left-lung. Many geometric/anatomical parameters were measured in the FB condition: heart and left-lung volumes (Vheart, Vlung-L), maximum thickness of the same organs inside the tangential fields (dheart, dlung-L), axial and para-sagittal cardiac contact distances (CCDax, CCDps), maximum tangential distance between beam-entrance and beam-exit (dentrance-exit), maximum anteroposterior diameter of the chest. Results: DIBH plans showed a significant reduction of Dmean (−60.9%), V5Gy (−82.5%), V20Gy (−93.6%) and (−95.8%) of the heart (p < 0.01, Wilcoxon signed-rank test), while no significant difference in target coverage and left-lung V5Gy, V20Gy. The parameters that significantly correlated with Δ DBH-FB were: Vheart (0.041 < p < 0.049, 0.63 < R < 0.65), dheart (p < 0.001, 0.96 < R < 0.97), CCDps (0.036 < p < 0.045, 0.64 < R < 0.66) and dentrance-exit (0.036 < p < 0.048, 0.64 < R < 0.67). Conclusions: This study confirmed how DIBH for left breast cancer treatment can decrease cardiac dose. The benefit of DIBH over FB strictly depends on chest shape, heart size and heart position. However, most of the parameters showed a weak correlation with Δ DBH-FB, so they cannot be used to effectively predict Δ DBH-FB. Only dheart seems to be a good predictor of Δ DBH-FB, but more cases must be included to confirm/reject these findings.